An electromyographic study on the sequential recruitment of bilateral sternocleidomastoid and masseter muscle activity during gum chewing. (22nd June 2017) - Guo, S.‐X.; Li, B.‐Y.; Zhang, Y.; Zhou, L.‐J.; Liu, L.; Widmalm, S.‐E.; Wang, M.‐Q.
Summary: Mandibular functions are associated with electromyographic activity of the jaw muscles and also the sternocleidomastoid muscle (SCM). The precise spatiotemporal relation of SCM and masticatory muscles activities during chewing is worthy of investigation. To analyse the sequential recruitment of SCM and masseter activities during chewing as indicated by the spatiotemporal locations of their activity peaks. Jaw movements and bilateral surface electromyographic activity of SCM and masseter were recorded during gum chewing in 20 healthy subjects. The timing order was decided by comparing the length of time from the time when the opening started to the time when the surface electromyographic activity reached its peak value. Spatial order was analysed by locating the peak electromyographic activity onto a standard chewing cycle which was created based on 15 unilateral chewing cycles. Paired t ‐test, one‐way ANOVA and Student–Newman–Keuls post‐test were used for comparisons. Although the Time to Peak for the balancing side SCM appeared shorter than for the other three tested muscles, most often it did not reach a level of significance. However, the location of the balancing side SCM's peak activity was further from the terminal chewing position (TCP) than the working side SCM and bilateral masseters ( P < 0·05). The balancing side SCM activity reached its peak significantly further away from TCP than the other three tested muscles during chewing. Further studies with spatiotemporal variables included should be helpful to understand the roles of the head, neck and jaw muscles in orofacial and cervical dysfunctional problems.